The Morphology of Cscha Circumbinary Disk Suggesting the Existence of a Saturn-Mass Planet - Perez-Marquez, S (EDP Sciences, 2022)
Context. Planets have been detected in circumbinary orbits in several different systems, despite the additional challenges faced during their formation in such an environment. Aims. We investigate the possibility of planetary formation in the spectroscopic binary CS Cha by analyzing its circumbinary disk. Methods. The system was studied with high angular resolution ALMA observations at 0.87 mm. Visibilities modeling and Keplerian fitting are used to constrain the physical properties of CS Cha, and the observations were compared to hydrodynamic simulations. Results. Our observations are able to resolve the disk cavity in the dust continuum emission and the 12CO J:3-2 transition. We find the dust continuum disk to be azimuthally axisymmetric (less than 9% of intensity variation along the ring) and of low eccentricity (of 0.039 at the peak brightness of the ring). Conclusions. Under certain conditions, low eccentricities can be achieved in simulated disks without the need of a planet, however, the combination of low eccentricity and axisymmetry is consistent with the presence of a Saturn-like planet orbiting near the edge of the cavity. © N. T. Kurtovic 2022.